An overview of the knowledge, perception and experience of dentists about the utilization of teledentistry as a dental care media in Makassar, Indonesia - Rasmidar Samad; Burhanuddin D. Pasiga; Nursyamsi Nursyamsi; Alex Aryanto (Journal of Dentomaxillofacial Science, 2021)
Objective: To describe the characteristics, knowledge, perceptions and experiences of dentists regarding the use of teledentistry in Makassar, Indonesia.Methods: A cross-sectional survey with 87 dentists in Makassar as respondents. The service was carried out by distributing questionnaires in the form of statements and questions regarding the use of teledentistry as a dental care medium. This study used univariate analysis.Results: Most of the respondents were aged 31-40 years (43.7%) and 71.3% of the respondents were women. As many as 60.9% of respondents have good knowledge about the use of teledentistry. As many as 80.5% of respondents have a good perception of the use of teledentistry. As many as 58.6% of respondents have no experience in using teledentistry. Conclusion: Generally dentists in Makassar already have a good knowledge in understanding teledentistry as utilization. dental care media. Generally dentists in Makassar have a good perception in interpreting the use of teledentistry as dental care media. Most of the dentists have no experience in the use of teledentistry as dental care media.